Para além do acesso à ciência e à tecnologia, a compreensão da realidade na sua concretude como um elemento preponderante para a profunda transformação social: relações entre Karl Marx e a pedagogia histórico-crítica - Schwede, Marcos Aurelio (2022)
Considering the current historic moment which is the expression of the capitalist society, it was analyzed how access to scientific knowledge can be decisive to a profound social transformation. This is a bibliographic research in which two theories were studied in parallel, the theoretical production of KarI Marx and Historical-Critical Pedagogy theory. This research was conducted using historical and dialectical materialism methods. Starting from the most relevant theoretical productions, successive analyses of the selected content were made defining categories and structures in the process, resulting in theoretical explanations for the complex presented reality. In the last phase the process was reversed, making new connections inside the created structure itself, and also connecting it with the social historic reality. As a result, it was possible to understand that science and technology can have a deep meaning to society and also materialities and their inherent social objectivities could exist as fundamental parts of humanity. However science and technology are also an expression of the current historical period and thus intrinsically linked to hegemonic interests, reality falsehood, and human and environmental degradation. From that relationship and broad human society theory, a thesis was formulated that access to understanding the reality is fundamental and predominant to deep social transformation. Comprehending reality as a whole needs a different epistemology and gnoseology apart from the ones used when science serves capitalism. When analyzing Historical-Critical Pedagogy, it is possible to see that it promotes workers’ access to the understanding of reality as a whole under some circumstances, but it also hinders and tries to deny it when scientific knowledge is working for capitalism. These two viewpoints are revealed as an expression of a complex social connection, to which those who are looking for social transformation are presented. For those who act on behalf of this pedagogy, it is possible to identify an aspiration to promote the comprehension of reality as a whole, which however, does not create a solid foundation when it is not a priority, or even when diluted alongside other proposals. In current history radical action is needed, considering the theoretical use of the word. Under these circumstances, an education aspiring a deep social transformation needs to enable the understanding of the reality as a whole by the subjects, and by their own constructivists movements – reality which is built on multiple historic relations, objectives and contradictions, and also by hegemonic interests that drive social reality. The construction of different needs is fundamental to a diverse society which can enjoy free life built by the needs of their own education. Finally, creating a workers’ political body is essential to their own organization and own formation só that they can take action on building a deeply transformed society.